2018
DOI: 10.1039/c7ra13490h
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient nano-sized Cu2O/SiO2egg-shell catalyst for C–C coupling reactions

Abstract: Mesoporous SiO2-supported Cu2O nanoparticles as an egg-shell type catalyst were prepared by impregnation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Only two examples of Cu 3 N/SiO 2 materials exist in the literature [ 67 , 68 ]. The impregnation of SiO 2 by a Cu(II) salt in solution followed by deposition–precipitation is an effective way to fabricate oxidic copper-based SiO 2 composites [ 69 , 70 ]. We have shown that such combined impregnation−deposition–precipitation approaches work equally well for nitride-SiO 2 composites.…”
Section: Resultsmentioning
confidence: 99%
“…Only two examples of Cu 3 N/SiO 2 materials exist in the literature [ 67 , 68 ]. The impregnation of SiO 2 by a Cu(II) salt in solution followed by deposition–precipitation is an effective way to fabricate oxidic copper-based SiO 2 composites [ 69 , 70 ]. We have shown that such combined impregnation−deposition–precipitation approaches work equally well for nitride-SiO 2 composites.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a mesoporous polymer-supported Cu NPs catalyst was developed [65] and applied to palladium-and solvent-free coupling of acid chloride and aryl alkynes. Similar experimental conditions were used in the acylation of aryl acetylenes with benzoyl chloride promoted by a nanosized Cu2O/SiO2 egg-shell catalyst [66]. Finally, Moghaddam and coworkers [67] reported the application of cobalt-copper ferrite nanoparticles (CoCuFe2O4), obtained by the coprecipitation method, to the synthesis of alkynyl ketones by acyl Sonogashira reactions.…”
Section: Copper-based Catalysts For Acyl Sonogashira Reactionsmentioning
confidence: 95%
“…These observations veried no clogging of pores with copper species. 73 The specic pore volume increased aer supporting NP with copper nitrate. Aer loading Cu(II), larger pores generated; as a result, the average pore diameter increased from 12.73 to 19.70 nm.…”
Section: Characterization Of Cu(ii)/np Catalystmentioning
confidence: 99%